Anabolic-androgenic steroids. Mechanism of action and clinical effects - Daria Matyja; Leila Abod; Natalia Ilnicka; Maria Sadlik; Patrycja Zuziak (Kazimierz Wielki University, 2023)
Introduction and aim. Anabolic-androgenic steroids (AAS) are used for the rapid enhancement of muscular mass and optimization of athletic performance. Their administration is frequently linked with a plethora of adverse health implications. The primary objective of this study is to provide a comprehensive analysis of multifaceted impacts of anabolic-androgenic steroids on the human body. Material and methods. A review of literature was performed by searching PubMed and GoogleScholar databases using the following key words: anabolic-androgenic steroids, muscular hypertrophy, female masculinization. Analysis of the literature. Anabolic-androgenic steroids are synthetically manufactured derivatives of testosterone. Given the widespread distribution of the androgen receptor, the effects of these steroids are broad, influencing almost all bodily functions. Their impacts include, promoting muscular hypertrophy including that of the cardiac muscle, premature epiphyseal closure, liver diseases, masculinization in females, feminization in males, and degradation in sperm quality. Conclusion. AAS consumption is a significant public health problem. While they may appeal to users by enhancing their physical attractiveness they carry multiple health consequences. Patients should be educated about the adverse effects of taking AAS so they can make informed decision about starting or stopping their use.